Questionnaires of the Kazan Doctors of the First Years of Soviet Rule as a Historical Source - Khaziakhmetova, Raniia; Salnikova, Alla (Journal of History Culture and Art Research, 2018)
The relevance of this problem is put into need of deeper and comprehensive study of the early Soviet social policy and practice of creating structure of the society capable to realize social claims of the young Soviet state. A specific place among them was held by creating system of the public health care sent to the period of a boundary of the 1910th, most difficult for the Soviet country, - the 1920th years not so much on improvement of quality of life of the Soviet citizens how many on preservation of this life, per se. Among the main groups of the actors who were responsible for realization of this important task there were not only organizers of new Soviet medicine, but also community of the Soviet doctors, very non-uniform from the point of view of the socio-political characteristics. Considering the high need for health workers in the conditions of civil war and sharp falling of the standard of living of the population, the Soviet power was terribly interested in creating necessary mechanisms of accounting of this social group on the basis of a number of criteria, including criterion "kin" − "stranger". One of possible ways of such account and identification of identity were registration cards of doctors. In article the analysis more than two hundred such cards collected by Public health department of the Kazan provincial executive committee of Council of working, country and Red Army deputies at the end of September, 1918 right after liberation of Kazan from Komuchevets and White Czechs is given. The carried-out analysis allowed creating a certain collective portrait of medical community of Kazan on the basis of application of a method of a prosopography as creating the collective biography of the studied social group. Results of a research consist in the characteristic of such group of people, poorly studied from the sociopolitical and sociocultural point of view, as representatives of medical community of the first years of the Soviet power perceived, on the one hand, as an important labor and professional resource, and, with another as possible object of "re-education" of "bourgeois experts" on the new, Soviet beginnings. The work technique with such low-studied source as registration cards of doctors is offered. Materials of article can be used for teaching socio-political history of Russia, history of health care and medicine, history of the intellectuals, a source study of office work documentation and also daily occurrence history.